Quantitative Analysis of Multiparty Tariff Negotiations - Bagwell, Kyle; Staiger, Robert W.; Yurukoglu, Ali (Econometrica, 2021)
We develop a model of international tariff negotiations to study the design of the institutional rules of the GATT/WTO. A key principle of the GATT/WTO is its most‐favored‐nation (MFN) requirement of nondiscrimination, a principle that has long been criticized for inviting free‐riding behavior. We embed a multisector model of international trade into a model of interconnected bilateral negotiations over tariffs and assess the value of the MFN principle. Using 1990 trade flows and tariff outcomes from the Uruguay Round of GATT/WTO negotiations, we estimate the model and use it to simulate what would happen if the MFN requirement were abandoned and countries negotiated over discriminatory tariffs. We find that if tariff bargaining in the Uruguay Round had proceeded without the MFN requirement, it would have wiped out the world real income gains that MFN tariff bargaining in the Uruguay Round produced and would have instead led to a small reduction in world real income relative to the 1990 status quo.